Development of high school physics class XI book, based on concept map to enhance the high-level thinking skills (HOTS). (March 2020) - Gusnedi, G; Ratnawulan, R; Putra, A
Abstract: Low high-level thinking skills (HOTS) of students, especially in physics can not be separated from the process of learning activities of students in schools that have not emphasized the student-centered. One problem is the books or reading material that is used by high school physics students and teachers have not led to the aspects of cognitive domains that are part of high-level thinking skills. Based on those developed for high school physics textbook using concept maps in both the material and the exposure to examples and exercises for students. The study aims to gain if the book is worth to be used in schools. Development model used in this study is a model of Plomp. ModelPlomp consists of three stages of development that preliminary research (initial investigation), prototyping phase (phase prototypes) and assessment phase (phase assessment). To assess the feasibility of this book used some experts consisting of several professors of physics and school physics teacher. The results of the feasibility test of power obtained an average score of 3.65 with very good category. Feasibility in terms of the depth of material, kesesuai with the development of the students thought patterns and linkage map concept with high-level thinking skills. While the results of feasibility assessment of conformity with the curriculum, the ease of understanding the text, the feasibility of the exercise presented by the teachers obtained a score of 3.80. The results of the feasibility test of power obtained an average score of 3.65 with very good category. Feasibility in terms of the depth of material, kesesuai with the development of the students thought patterns and linkage map concept with high-level thinking skills. While the results of feasibility assessment of conformity with the curriculum, the ease of understanding the text, the feasibility of the exercise presented by the teachers obtained a score of 3.80. The results of the feasibility test of power obtained an average score of 3.65 with very good category. Feasibility in terms of the depth of material, kesesuai with the development of the students thought patterns and linkage map concept with high-level thinking skills. While the results of feasibility assessment of conformity with the curriculum, the ease of understanding the text, the feasibility of the exercise presented by the teachers obtained a score of 3.80.